Soils & Fertilizers for Master Gardeners: Soil Organic Matter and Organic Amendments - Gurpal S. Toor; Amy L. Shober (EDIS)
Revised! SL-273, a 3-page illustrated fact sheet by Gurpal S. Toor and Amy L. Shober, educates homeowners about the importance of soil organic matter and provides suggestions about how to build the organic matter in garden and landscape soils. It is part of a series entitled Soils and Fertilizers for Master Gardeners. Includes references. Published by the UF Department of Soil and Water Science, January 2009.